2013
DOI: 10.3892/mco.2013.198
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of fatty acid-binding proteins and pathological implications in the progression of tongue carcinoma

Abstract: Abstract. Tongue carcinomas are common malignancies of the oral cavity. Understanding the molecular mechanisms behind the disease progression is a prerequisite for improving patient prognosis. Fatty acid-binding proteins (FABPs) are cytoplasmic lipid chaperones that affect cellular organization and energy production. Although their aberrant expression is involved in carcinoma progression, its role in the pathology of tongue carcinomas remains unclear. In the present study, the immunohistochemical expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…A comparison of normal cells with benign hyperplasia indicates that FABP5 is ubiquitously overexpressed in most the cancers including breast cancer, cervical cancer (CCa), endometrial cancer (EC), head and neck squamous cell carcinoma (HNSC), prostate cancer (PCa), hepatocellular carcinoma (HCC), tongue carcinoma, esophageal cancer (ESCA), clear cell renal cell carcinoma (ccRCC), stomach adenocarcinoma (STAD), and lung squamous cell carcinoma (LUSC) ( Table 2 ). Mechanism studies have revealed that FABP5 regulates tumorigenesis and cancer progression by regulating different pathways including MMP-2/MMP-9, PI3K/AKT, and PPARs pathways ( Rauch et al, 2004 ; Shi et al, 2012 ; Forootan et al, 2014 ; Ohyama et al, 2014 ; Nitschke et al, 2020 ) ( Figure 7 and Table 2 ). Ki67, a notable cell proliferation marker in the tumor, could independently predict cancer progression ( Yang et al, 2018 ).…”
Section: Biological Functions Of Fabp5mentioning
confidence: 99%
“…A comparison of normal cells with benign hyperplasia indicates that FABP5 is ubiquitously overexpressed in most the cancers including breast cancer, cervical cancer (CCa), endometrial cancer (EC), head and neck squamous cell carcinoma (HNSC), prostate cancer (PCa), hepatocellular carcinoma (HCC), tongue carcinoma, esophageal cancer (ESCA), clear cell renal cell carcinoma (ccRCC), stomach adenocarcinoma (STAD), and lung squamous cell carcinoma (LUSC) ( Table 2 ). Mechanism studies have revealed that FABP5 regulates tumorigenesis and cancer progression by regulating different pathways including MMP-2/MMP-9, PI3K/AKT, and PPARs pathways ( Rauch et al, 2004 ; Shi et al, 2012 ; Forootan et al, 2014 ; Ohyama et al, 2014 ; Nitschke et al, 2020 ) ( Figure 7 and Table 2 ). Ki67, a notable cell proliferation marker in the tumor, could independently predict cancer progression ( Yang et al, 2018 ).…”
Section: Biological Functions Of Fabp5mentioning
confidence: 99%
“…Cytoplasmic FABP5 levels are elevated in human head and neck squamous cell carcinomas (Han et al, 2009). Elevated cytoplasmic FABP5 levels have also been documented in advanced tongue carcinomas (Ohyama et al, 2014).…”
Section: Other Cancersmentioning
confidence: 99%
“…En el presente trabajo revelamos, mediante ensayos bioinformáticos, que los niveles de expresión de FABP5 correlacionan con una menor probabilidad de supervivencia específicamente en LUAD, dado que no tiene valor pronóstico en LUSC. La relación de FABP5 con la diferenciación, metástasis y pronóstico en tumores escamosos no es clara y distintos estudios han mostrado resultados variables [213,214]. Las alteraciones moleculares específicas de LUSC y LUAD que conllevan al comienzo y la progresión tumoral podrían explicar la diferencia entre los mismos [215][216][217].…”
Section: Discussionunclassified